Analysis of chemokine gene expression in lung cells by polymerase chain reaction - Petrek, M (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1999)
The article describes a polymerase chain reaction (PCR) based method for semiquantitative assessment of mRNA expression for chemotactic cytokines in the lower respiratory tract cells. Cytokine mRNA was detected using PCR preceded by reverse transcription of mRNA into cDNA. The procedures of RNA extraction and of reverse transcription-PCR assay are described in the first part of the article. The second part demonstrates optimalisation experiments performed to ensure specificity, accuracy and reproducibility of the RT-PCR assay and discuss the approach to mRNA quantification using normalisation of cytokine mRNA expression to the expression of beta-actin mRNA.
Keywords: Transcription, Genetic; Reverse Transcriptase Polymerase Chain Reaction; genetická transkripce; Lung; RNA, Messenger; Chemokines; bronchoalveolární lavážní tekutina; Humans; lidé; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; chemokiny; plíce; Bronchoalveolar Lavage Fluid